2020
DOI: 10.1038/s41598-020-74780-9
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological correlates of the brain-derived neurotrophic factor (BDNF) Val66Met polymorphism

Abstract: The brain-derived neurotrophic factor (BDNF) protein is essential for neuronal development. Val66Met (rs6265) is a functional polymorphism at codon 66 of the BDNF gene that affects neuroplasticity and has been associated with cognition, brain structure and function. The aim of this study was to clarify the relationship between BDNF Val66Met polymorphism and neuronal oscillatory activity, using the electroencephalogram (EEG), in a normative cohort. Neurotypical (N = 92) young adults were genotyped for the BDNF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…In these studies, COMT Val homozygotes were found to have lower a power than Met homozygotes (Bodenmann et al, 2009), and COMT polymorphism was found to influence phase-resetting of g oscillations in attention (Garcia-Garcia et al, 2017). Furthermore, BDNF has been implicated in resting-state oscillation amplitude differences in delta (0.5-3.5 Hz), a, and b bands but not in q band amplitudes (Roy et al, 2020) and in reduced g band FC between anterior and posterior regions in Val/Met compared to Val/Val participants (Rodrı ´guez- Rojo et al, 2018). We used here a data-driven approach for mapping the effects of COMT and BDNF polymorphism on both instantaneous oscillation amplitudes and their LRTCs from sourcereconstructed MEG data.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In these studies, COMT Val homozygotes were found to have lower a power than Met homozygotes (Bodenmann et al, 2009), and COMT polymorphism was found to influence phase-resetting of g oscillations in attention (Garcia-Garcia et al, 2017). Furthermore, BDNF has been implicated in resting-state oscillation amplitude differences in delta (0.5-3.5 Hz), a, and b bands but not in q band amplitudes (Roy et al, 2020) and in reduced g band FC between anterior and posterior regions in Val/Met compared to Val/Val participants (Rodrı ´guez- Rojo et al, 2018). We used here a data-driven approach for mapping the effects of COMT and BDNF polymorphism on both instantaneous oscillation amplitudes and their LRTCs from sourcereconstructed MEG data.…”
Section: Discussionmentioning
confidence: 95%
“…Prior observations about COMT and BDNF polymorphism effects on electrophysiological activity are scarce and mainly restricted to EEG and MEG sensor level (Bodenmann et al, 2009;Bonetti et al, 2021;Garcia-Garcia et al, 2017;Rodrı ´guez-Rojo et al, 2018;Roy et al, 2020). In these studies, COMT Val homozygotes were found to have lower a power than Met homozygotes (Bodenmann et al, 2009), and COMT polymorphism was found to influence phase-resetting of g oscillations in attention (Garcia-Garcia et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We could not examine the causal relationship between BNDF level and reduction in activity in patients with NAFLD in this study. Although the biological significance of BNDF in the reduction in activity remains unclear, BDNF has been reported to be modulated by various factors, including race [ 43 ], depressive symptoms [ 44 ], cognitive function [ 45 ], and genetic polymorphism [ 46 , 47 ]. These factors might be involved in the negative association between serum BDNF levels and activity in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Met substitution damages the activity-dependent secretion and intracellular distribution of BDNF in hippocampal neurons ( 53 ). Compared with Val carriers, Met carriers have worse episodic memory and hippocampal function, and the gray matter volume of the prefrontal lobe and temporal lobe is smaller ( 54 ).…”
Section: Mechanism Of Aging and Neurodegenerative Diseases On Cogniti...mentioning
confidence: 99%